Pit slope depressurisation investigation for an open cut iron ore mine in the Pilbara - Dodman, A; Beale, G; Rodriguez, J; Cottrell, A; Youngs, J (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Iron ore mining operations in the Pilbara region of Western Australia are currently undergoing unprecedented growth. Expansion of active open cut mines and development of new deposits below the pre-mining water table, present significant challenges in terms of general mine dewatering and pit slope depressurisation. Studies to characterise pore pressure behaviour have become a key component of the mining cycle. Pore pressure inputs to geotechnical slope stability assessments and timely implementation of mine drainage is essential to optimise slope design, performance and safety. This paper presents a case study of a staged hydrogeological study for a large highwall at an active iron ore mine in the Pilbara. The primary objective was to characterise pore pressures, provide input to slope design studies and support management of pit slope depressurisation, ahead of an aggressive pushback. The bulk stratigraphy is structurally complex, defined by alternating banded iron formation (BIF) and shale macro-band sequences. Key geotechnical issues include a number of fault structures identified behind the final pit wall which may require a high level of advanced depressurisation, saturated low permeability footwall shale units and potential hydraulic connectivity between the local orebody groundwater system and a regional dolomite aquifer. Installed vibrating wire piezometers (VWPs) show a strong response to pumping within the mineralised BIF. In contrast, high pore pressures prevail within the deep shale units. The study demonstrates the importance of integration between hydrogeological and geotechnical programs to provide adequate planning for the design and implementation of dewatering and slope depressurisation systems, and presents key learning outcomes for similar environments.